(3GdEcdjd aj CfSGH MejQ hCjGe edhcgGs - (3GdMSf Hf CMeO Hf jYbhH GdgeOGfj , GHf GdMGFc , CHh eMeO,J (B334 (3g` s
(3ChdgG (B:s
(3HGH eG LGA ai PcQ bUhQ Gdjef heYGbdgG , heG bjd ef GdTYQ , heG ajgG ef GdCNHGQ CbOe TF bUQ ZeOGf bGd GdgeOGfi (B: (3Chd bUhQ Gdjef hC(B'(3LHgG PcQkG s
(3BNQgG (B:s
(3BNQg ai PcQ Gdedc Pi fhGS (B" (3hbGd YdbeI Hf Pi LOf (B:" (3Cda edc SaGge GdOgQ cCSkG eQI RdRdJ Hge cd CQV s
(3YdjgG Jedc HGSe GdSjO Ydi Hf CMeO Hf MSf GdYWGSs
(3hBd GdYWGS ai MQjVI heSLd Ydi GdUaMI GdChdi JGQNj (B1282(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B204 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B269s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTYHjg GdecdG (B(179) s
Keywords: (3GdJGQjNs